Konsep Pembelajaran Tahfidz al Qur’an Juz 30 dan Implementasinya pada Anak Usia Dini - A. Syafi’ AS. (MODELING: Jurnal Program Studi PGMI, 2019)
Learning tahfidz Al Qur'an Juz 30, which contains short letters, really needs to be implemented in children from an early age, so that the child's soul is planted with a strong faith, is motivated to learn to obey the rules of Allah's shari'at then can practice it according to the shari'ah The God. This research is a library research using a qualitative approach. The data collection uses documentation techniques, while the data analysis technique uses qualitative descriptive analysis techniques. The results of this study indicate that in learning tahfidz Al Qur'an juz 30 in early childhood there are several models of methods of memorizing the Qur'an, including, 1) Bi-Nadzar Method, 2) Tahfidz Method, 3) Talaqqi Method, 4) Method Takriri, and 5) Tasmi 'Method.